IMPACT OF FIRES IN DIFFERENT MANAGEMENT SYSTEMS ON THE AREIA BRANCA FARM IN THE MUNICIPAL OF POMBAL- PB - BRAZIL - Alves Fernandes, Ronaldo; Souto, Patrícia Carneiro; Souto, Lauter Silva; Maracaja, Patricio Borges; Sousa, Luci Cleide Farias Soares (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2011)
The burning of pasture and crop residues in the period prior to the rains in the semi-arid region is a practice usually applied by farmers to facilitate cleaning of the area and renew pasture. This study aimed to evaluate the effect of fire in chemical and biological soil properties in different areas in the hinterland of Paraíba. The treatments consisted in the use of fire and grazing in an area of growing with and no use of fire in grassland and preserved savanna area that served as a witness. Samples were collected bimonthly from September 2008 to July/2009. Samples were collected at depth of 0-20 cm in each area, for analysis of chemical indicators. To determine the biological indicators were installed traps "Provid" which consisted in the use of plastic bottles for collection of soil macrofauna, the soil samples without problems to determine the mesofauna were extracted using the type extractors modified Berlese-Tullgren (Oliveira 1999). Composed of rectangular boards, each containing structure, 25W lamps divided in two upper compartments contains rings with the samples and the lamps, while in the lower compartment are funnels and bottles of glass with a solution of ethyl alcohol 80% to the collection of organisms. The largest number of individuals of the mesofauna was collected in the areas of native grassland and savanna preserved without burning. As for the macrofauna, the capture of the organisms was higher in the area of native pasture without burning. The pH values were analyzed were near the neutrality, mainly suffering major reductions in CCQ. In burned areas (PNQ and CCQ) showed increased levels of P and K after burning and then there was a reduction in the levels.